Evaluation of The Health Services Program in the Posyandu for the Elderly, the Working Area of the Sungai Pakning Puskesmas, Bengkalis Districtyear 2023 - Reva Khairani*; Kiswanto Kiswanto; Hetty Ismainar (Universitas Syiah Kuala, 2023)
Elderly Integrated Service Post is a public health effort in an elderly health program that aims to maintain the health and socio-economic productivity of the elderly. The Sungai Pakning Health Center has implemented an elderly health service program at the elderly Integrated Service Post but the program coverage is still low, namely 33% in 2022. The aim of the study was to evaluate health services at the elderly Integrated Service Post in the Work Area of the Sungai Pakning Health Center, Bengkalis Regency in 2023 using the CIPP method with context indicators input, process and product (output). This type of research is qualitative with a case study approach. There were 12 informants consisting of program holders for elderly services in Bengkalis Regency, persons in charge of the Sungai Pakning elderly health service program, doctors in charge, midwives, health promotion officers, cadres, the elderly and community leaders. The triangulation used is the triangulation of sources, methods and data. The results of the study show that the context (needs, problems, assets and opportunities) has been identified, inputs (human resources, funding, facilities and infrastructure) are still lacking for elderly Integrated Service Post activities, processes (promotive efforts, recording and reporting, monitoring and evaluation) have been carried out well, while preventive efforts are not in accordance with technical guidelines. The output has not reached the Bengkalis Regency target because the participation of the elderly in participating in elderly Integrated Service Post activities is still low, namely 33%. The health center can facilitate the formation of partnerships in each village through CSR with the private sector, businesses and community donations in facilitating facilities and infrastructure for the elderly Integrated Service Post. Community Health Centers can innovate digital-based counseling through Whatsapp Groups with elderly members or elderly families